2016
DOI: 10.1039/c6ob01248e
|View full text |Cite
|
Sign up to set email alerts
|

Identification of novel small-molecule inhibitors targeting menin–MLL interaction, repurposing the antidiarrheal loperamide

Abstract: Leukemia with a mixed lineage leukemia (MLL) rearrangement, which harbors a variety of MLL fusion proteins, has a poor prognosis despite the latest improved treatment options. Menin has been reported to be a required cofactor for the leukemogenic activity of MLL fusion proteins. Thus, the disruption of the protein-protein interactions between menin and MLL represents a very promising strategy for curing MLL leukemia. Making use of menin-MLL inhibitors with a shape-based scaffold hopping approach, we have disco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 77 publications
0
10
0
Order By: Relevance
“…There are other inhibitors of the Menin–MLL1 interaction, including macrocyclic peptidomimetic compound MCP-1 [ 118 ], a peptidomimetic compound 25 [ 62 ], VTP-50469 [ 63 ] [ 64 ], neomycin [ 65 ], tobramycin [ 65 ], loperamide [ 66 ], DCZ_M123 [ 67 ], DC-YM21 [ 66 ], and cytisine derivative 1a [ 68 ].…”
Section: Ppis Involving Wt-mll1mentioning
confidence: 99%
“…There are other inhibitors of the Menin–MLL1 interaction, including macrocyclic peptidomimetic compound MCP-1 [ 118 ], a peptidomimetic compound 25 [ 62 ], VTP-50469 [ 63 ] [ 64 ], neomycin [ 65 ], tobramycin [ 65 ], loperamide [ 66 ], DCZ_M123 [ 67 ], DC-YM21 [ 66 ], and cytisine derivative 1a [ 68 ].…”
Section: Ppis Involving Wt-mll1mentioning
confidence: 99%
“…In this context, there have been successful de novo designed small molecule inhibitors of the MLL-menin interaction, such as members of the thienopyrimidine class ( Shi et al, 2012 ; Senter et al, 2015 ; Borkin et al, 2016 ). The crystal structures of the inhibitors MI-2-2 and MIV-6R were used in scaffold hopping calculations that as a result suggested loperamide, an antidiarrheal drug used in acute and chronic diarrhea as well as in ileostomy, as a possible inhibitor of the interaction between MLL and menin ( Yue et al, 2016 ). Similarly to molecules that disrupt the MLL-menin interaction, histone deacetylase (HDAC) inhibitors also affect the transcription-regulatory machinery governing the epigenetic changes that drive leukemogenesis.…”
Section: Hypothesis Driven and Target-based Strategies For Drug Repurposing In Mll -Rearranged Leukemiamentioning
confidence: 99%
“…As a shape-based three dimensional structure superposition method, it has been extensively used to generate potential alternatives of known compounds based on the bioisosteric replacement of core motif within molecules (Sun et al, 2012 ; Lamberth, 2017 ). In 2016, Yue et al applied a shape-based scaffold hopping approach to reposition approved drugs targeting the Menin-MLL1 interaction (Yue et al, 2016 ). In the study, reported bioactive conformations of representative Menin-MLL1 inhibitors MI-2-2 and MIV-6R (PDB code 4GQ4 and 4GO8, respectively) were used as query (Shi et al, 2012 ; He et al, 2014 ).…”
Section: Wdr5-mll1mentioning
confidence: 99%